Moral Pajak, Sanksi Pajak, Penerapan E-Filling dan Kepatuhan Pajak - Nugroho, Wawan Cahyo (E-Jurnal Akuntansi; Vol 31 No 11 (2021), 2021)
This study aims to obtain empirical evidence regarding the effect of tax morale, tax sanctions and the application of e-filling on tax compliance. This research is quantitative research. Data collection techniques in the study used an online questionnaire with a sample of 65 respondents. Technical data analyst using multiple linear regression. The results showed that tax morale and the application of e-filling had a positive effect on tax compliance. This shows that taxpayers who work in Surabaya have a spirit that comes from within themselves and have a high awareness that the taxes they deposit to the state treasury are mandatory contributions which will later be used for the construction of public facilities. The tax reporting system with e-filling will make it easier and provide convenience for taxpayers to report their taxes faster. Meanwhile, tax sanctions have no effect on tax compliance. This shows that taxpayers still think that the implementation of tax sanctions is less strict and the lack of socialization of regulations and taxpayers do not understand the risks if taxpayers do not report their taxes. Keywords : Morale; Sanctions; E-Filling; Tax Compliance.